2013
DOI: 10.1016/j.cmpb.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical simulation of the fetal descent without imposed theoretical trajectory

Abstract: Abstract-The medical training concerning childbirth for young obstetricians involves performing real deliveries, under supervision. This medical procedure becomes more complicated when instrumented deliveries requiring the use of forceps or suction cups become necessary. For this reason, the use of a versatile, configurable childbirth simulator, taking into account different anatomical and pathological cases, would provide an important benefit in the training of obstetricians, and improve medical procedures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 27 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…The three-dimensional solid models were obtained from static images of MRI using free software segmentation ITK-SNAP based on the evolution of an active contour. The models, including geometry and material parameters, are provided by the SAARA Team of LIRIS of University of Lyon 1 as described in [51]. The fetus model includes 4430 tetrahedral elements and 1128 nodes (Fig.…”
Section: Comparison With Finite Element Methodsmentioning
confidence: 99%
“…The three-dimensional solid models were obtained from static images of MRI using free software segmentation ITK-SNAP based on the evolution of an active contour. The models, including geometry and material parameters, are provided by the SAARA Team of LIRIS of University of Lyon 1 as described in [51]. The fetus model includes 4430 tetrahedral elements and 1128 nodes (Fig.…”
Section: Comparison With Finite Element Methodsmentioning
confidence: 99%
“…These cylinders have been sized according to the results from [11] and [12] which showed that the maximal applied force to extract the fetus is about 200N. The stroke of these cylinders have been chosen according to the trajectory extracted from Buttin et al [13] which is similar to the one introduced in Fig. 2.…”
Section: A Designmentioning
confidence: 99%
“…However, the number of research groups that are working in this area has increased and many are directly confronting these issues. More anatomical structures have been incorporated into modeling frameworks, less prescription for fetal head descent, and in some cases, fetal head molding has been taken into account . Population based models have also recently been developed for both the ‘passageway’ and the ‘passenger.’ These advances in the modeling frameworks are beginning to enable quantitative analysis of the mechanics of vaginal birth in order to identify the contributions of various anatomical structures to birth outcomes.…”
Section: Mechanics Of Deliverymentioning
confidence: 99%